Viral Gastroenteritis - Blacklow, Neil R; Cukor, George (The New England journal of medicine, 1981)
ACUTE infectious diarrheal illness is the leading cause of disease and death in many areas of the world. Indeed, by one estimate there were 3 to 5 billion cases of diarrhea accounting for 5 to 10 million deaths in Asia, Africa, and Latin America during the year 1977 to 1978. 1 Although the cause of a large proportion of this infectious gastroenteritis remains unknown, recently discovered viral agents have joined certain bacteria and parasites on the list of pathogens involved in serious diarrheal disease worldwide. Acute viral gastroenteritis is an extremely common illness that affects all age groups and occurs in . . .